THE STUDY OF TEACHING A FOREIGN LANGUAGE TO CHILDREN THROUGH THE COMMUNICATIVE METHOD - Tashpulatova, Mukambar (Журнал иностранных языков и лингвистики, 2023)
In this article we consider different methods of oral foreign language teaching in a specific situation. We claim that when learning a second language, in addition to phonological and lexical-grammatical knowledge, students need to master the way of communicating with other people. We emphasize the need to develop an integrated approach to the preparation and implementation of lessons and tasks for the effective development of students’ oral language skills.